Open Defecation Free Zone And Practice in Jorayal Gaunpalika - Pokhrel, Mukunda Raj (Butwal Campus Journal, 2020)
This study is based on Open Defecation Free Zone and Their Practice in Jorayal Gaunpalika -4, Doti District. The main objective of the study is to analyze the practice of open defecation free zone. Out of 310 total households, only 150 households were selected for the study. The cluster sampling method was applied to collect necessary information. The study area was divided into 6 clusters and from each cluster 25 households were selected randomly. According to the study, hand wash practice is very high, that is, 85.3 percent wash their hands with soap and water and 14.7 percent use soil and water. The high majority of the respondents (88.7%) said that they maintained the garden and the toilet, 7.3 percent said that they kept the courtyard of the house plain. Most of the respondents (82.7%) cleaned the toilet every day. Most of the respondents (70.7%) expressed that they defecated in the field, and 28.7 percent respondents said that they defecated along the riverside and remaining others used the road. Based on study findings, the government and non-government sectors are suggested to support such open defecation free zone area ensuring adequate environmental sanitation. The municipality should make people aware of the importance of a good environmental hygiene.